2019
DOI: 10.5194/essd-11-1437-2019
|View full text |Cite
|
Sign up to set email alerts
|

GLODAPv2.2019 – an update of GLODAPv2

Abstract: Abstract. The Global Ocean Data Analysis Project (GLODAP) is a synthesis effort providing regular compilations of surface to bottom ocean biogeochemical data, with an emphasis on seawater inorganic carbon chemistry and related variables determined through chemical analysis of water samples. This update of GLODAPv2, v2.2019, adds data from 116 cruises to the previous version, extending its coverage in time from 2013 to 2017, while also adding some data from prior years. GLODAPv2.2019 includes measurements from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 80 publications
(105 reference statements)
4
158
2
Order By: Relevance
“…The baseline value from which the various pH perturbations are estimated is pH 2002 , which is calculated from the observed total alkalinity (TA) and dissolved inorganic carbon (DIC) in GLODAPv2 (Olsen et al, ), where DIC is first adjusted to year 2002 using the atmospheric perturbation method as detailed in Appendix B of Lauvset et al (), and the assumption that TA does not change over time. Since few ship‐based observations of ocean carbonate chemistry are made in winter there is a recognized seasonal bias in the GLODAPv2 data product (Olsen et al, ), and hence in all calculations made using these data, which makes the data product challenging to use for the surface ocean. No attempt has been made to correct for this bias in this present work, although we note that this bias is primarily an issue for surface measurements and this analysis focuses on the ocean interior.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline value from which the various pH perturbations are estimated is pH 2002 , which is calculated from the observed total alkalinity (TA) and dissolved inorganic carbon (DIC) in GLODAPv2 (Olsen et al, ), where DIC is first adjusted to year 2002 using the atmospheric perturbation method as detailed in Appendix B of Lauvset et al (), and the assumption that TA does not change over time. Since few ship‐based observations of ocean carbonate chemistry are made in winter there is a recognized seasonal bias in the GLODAPv2 data product (Olsen et al, ), and hence in all calculations made using these data, which makes the data product challenging to use for the surface ocean. No attempt has been made to correct for this bias in this present work, although we note that this bias is primarily an issue for surface measurements and this analysis focuses on the ocean interior.…”
Section: Methodsmentioning
confidence: 99%
“…The red dot is IODP Site U1305. The section on the right is dissolved oxygen from GLODAPv2.2019 (Olsen et al, 2019) and is indicated on the map on the left by the red polygon. Major water masses Antarctic Bottom Water (AABW), Circumpolar Deep Water (CDW), and North Atlantic Deep Water (NADW) are indicated in the section.…”
Section: Introductionmentioning
confidence: 99%
“…The pH values were reported on total pH scale at 0 dbar of pressure and both at 25ºC and in situ temperature following the same procedure of GLODAP v2 (Olsen et al, 2019). A total of 12,220 measurements of pH on NBS scale were converted to the total scale using CO2SYS (Lewis and Wallace, 1998) for MATLAB (van Heuven et al, 2011) with pH and total alkalinity as inputs.…”
Section: Ph Measurementsmentioning
confidence: 99%